Harmoni vokal pada proses afiksasi dalam bahasa Jawa dialek Banten - Ubaidillah Ubaidillah (Universitas Lampung, 2021)
Banten dialect of Javanese, is a variant of the Javanese language in Java. As in other Javanese dialects, of course there are minor differences that cause the uniqueness of the dialect in the Javanese language. This difference is also found in the Banten dialect of Javanese, especially in vocal harmony. In standard Javanese, the word /toko/, if it followed by the suffix /-e/ will be pronounced [tokone] 'its shop', while in the Banten dialect of Javanese, the word /toko/ if it followed by the suffix /-e/ will be pronounced [tɔkɔne] 'its shop'. This paper discusses the vocal harmony that occurs in the Banten dialect of Javanese. Vowel phonemes, which have allophones, play a very important role in forming vocal harmony when there is an affixation process. By using the distributional analysis method with the ultimat constituent analysis, the researcher found that the vocal harmony process in the allophones produced from the five vocal phonemes of the Banten dialect of Javanese /i/, /e/, /a/, /o/, and /u/ are found in the affixation process, those are: (1) Sufix /-e/ 'genitive meaning', (2) Suffix /-i/, ‘imperative meaning', (3) suffix /-aken/ 'imperative and declarative meaning', and (4) Suffix /-en/ 'imperative meaning'.